2004
DOI: 10.1002/adma.200306031
|View full text |Cite
|
Sign up to set email alerts
|

Facile Microstructuring of Organic Semiconducting Polymers by the Breath Figure Method: Hexagonally Ordered Bubble Arrays in Rigid Rod‐Polymers

Abstract: using a solenoid coil with an iron core of 2.5 cm diameter. The core was positioned a couple of millimeters away from the substrate in order to provide a substantially uniform magnetic field over the extent of the substrate. This uniform magnetic field was sufficient to bias the magnetic moments of the beads in the direction perpendicular to the substrate. However, the same field had little effect on the magnetization of the micromagnets because of their very high shape anisotropy (extremely large magnetic ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(133 citation statements)
references
References 49 publications
2
128
1
Order By: Relevance
“…In another study, 8 honeycomb structures were prepared using six-arm star polystyrene (PS), and a strong correlation between the number of arms, arm length, end-group functionality, and pore diameter were demonstrated. Other polymers that were used for the fabrication of honeycomb structures have included random and block copolymers of polystyrene (PS), [9][10][11][12][13][14][15][16]23 poly-(2-vinyl pyridine) (P2VP), 17 poly(p-phenyleneethynylene) (PPE), 18,19 fluorinated PMMA copolymers, 20 and an amphiphilic copolymer containing dendronized poly(alkyl methacrylate) and linear poly(ethylene oxide) blocks. 21 The exploitation of a wide range of polymers for the successful fabrication of microporous structures using the breath figure methodology continues to generate considerable interest, and recent efforts are now focused on developing such patterned porosity on biocompatible polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 8 honeycomb structures were prepared using six-arm star polystyrene (PS), and a strong correlation between the number of arms, arm length, end-group functionality, and pore diameter were demonstrated. Other polymers that were used for the fabrication of honeycomb structures have included random and block copolymers of polystyrene (PS), [9][10][11][12][13][14][15][16]23 poly-(2-vinyl pyridine) (P2VP), 17 poly(p-phenyleneethynylene) (PPE), 18,19 fluorinated PMMA copolymers, 20 and an amphiphilic copolymer containing dendronized poly(alkyl methacrylate) and linear poly(ethylene oxide) blocks. 21 The exploitation of a wide range of polymers for the successful fabrication of microporous structures using the breath figure methodology continues to generate considerable interest, and recent efforts are now focused on developing such patterned porosity on biocompatible polymers.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although many lithographic techniques [3][4][5][6] are known for the successful fabrication of porous thin films, the breath figure approach has received considerable interest due to the simple, inexpensive, and robust mechanism of pattern formation. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Breath figures are derived from ordered micrometer-sized water droplets that form during vapor condensation onto a polymer solution surface. 22 The process, also known as the solvent evaporation method, occurs as an appropriate solvent evaporates under humid conditions, leading to a temperature decrease at the air-liquid interface and subsequent water condensation.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) periodic structures are attractive for a wide range of applications in optics, 1,2 optoelectronics, 3,4 photonics, 5 electronics, 6 magnetic materials, 7 and biotechnology. 8 A variety of self-assembled systems have been utilized as templates to produce well-ordered 2D structures with no need of lithography, including microphaseseparated block copolymers, 7,9 hexagonally ordered arrays (i.e., breath figures) made by the condensation of micronsize water droplets on the surface of a polymer solution, 10 self-assembly of colloidal crystals, 11 and self-organized mesoporous silica.…”
mentioning
confidence: 99%
“…At first, it was suggested that star-like and hyperbranched polymers promote formation of well-ordered structures [26,42], however, later it was demonstrated that linear polymers also give rise to the patterns, typical for the breath-figures self-assembly, such as depicted in Figure 2 [40][41]. It was suggested that coiled polymers (polystyrene) promote formation of breath-figures patterns [42]; on the other hand, rigid-rod conjugated polymers also gave rise to wellordered honeycomb reliefs [36]. The impact of the molecular weight of the polymer on the resulting pattern remains obscure, and the data reported by various groups are controversial [44][45][46].…”
Section: Impact Of the Polymer Aarchitecture And Physical Parameters mentioning
confidence: 99%